Equi-join table optimization technique for temporal data - Mohd Rahim, Mohd Shafry; Kurmin, A.; Wahid, T.; Daman, Daut (Zarqa Private University, 2007)

(untitled)
Temporal data management is significant to applications such as environmental management systems. It is to ensure that the process of data storing, retrieving and manipulation can be conducted in an efficient manner. The main focus of this research is on the retrieval of temporal data. Evidently, in the area of temporal data retrieval, the issue that is given most attention by researchers is how to speed up data retrieval time. In our research, we attempt to tackle this issue in an information system which stores hydrological data using a database that utilizes the cube method. As an end result, we managed to establish a technique called the equi-join table optimization technique that was implemented to an existing database system. This technique will also analyze a query statement with several possible query executions to determine the most possible optimum implementation. The outcome indicated that there is indeed an improvement concerning the data retrieval response time.